Lotus (Nelumbo nucifera) benzylisoquinoline alkaloids: advances in chemical profiling, extraction methods, pharmacological activities, and biosynthetic elucidation - Xue Wei; Minghua Zhang; Mei Yang; Collins Ogutu; Jing Li; Xianbao Deng (Vegetable Research)
As a member of the only two species in the Nelumbonaceae family, lotus (Nelumbo nucifera) accumulates abundant benzylisoquinoline alkaloids (BIAs) in almost all of its tissues. Evidence from both traditional and modern medicine suggest great potential of the lotus BIAs in developing novel drugs for the prevention and treatment of diverse life-threatening diseases. This review provides a comprehensive summary on the up-to-date advances in the chemical profiling, extraction methods, pharmacological activities, and biosynthesis of lotus BIAs. Currently, a total of 59 BIAs structurally belonging to the 1-benzylisoquinoline, aporphine, and bis-BIA categories have been identified in various lotus tissues, with their predominant accumulation in the leaf and plumule. In contrast to the common S-conformers in Ranunculales, most lotus BIAs are R-conformers. Solvent extraction is still the most widely used BIA extraction method in lotus at the industrial level, however, numerous greener and highly advanced extraction techniques have also been developed. High-performance liquid chromatography (HPLC) followed by electrospray ionization (ESI) and tandem mass spectrometry (MS/MS) techniques are currently the most commonly used methods for separation, quantification, and characterization of lotus BIAs. Moreover, the pharmacological activities of major BIAs isolated from lotus leaves and plumules are discussed, and their biosynthetic pathways proposed based on recent functional characterization studies of lotus BIA biosynthetic genes. Finally, a summary discussion is provided on the future research trajectories in elucidating lotus BIA biosynthesis, storage, and transportation, as well as their potential application in clinical drug development.